Bisoprolol transdermal patch treatment for patients with atrial fibrillation after noncardiac surgery: A single-center retrospective study of 61 patients. (February 2020) - Yasui, Taku; Oka, Toru; Shioyama, Wataru; Oboshi, Makiko; Fujita, Masashi
Objectives: Atrial fibrillation after surgery is associated with increased rates of heart failure and ischemic stroke, and extension of hospitalization. Bisoprolol is a β-blocker used to reduce heart rate and manage arrhythmias during atrial fibrillation. However, the safety and efficacy of bisoprolol transdermal patch treatment in patients with postoperative atrial fibrillation remain unclear. Methods: We retrospectively assessed the electronic health records of our hospital between September 2013 and July 2018 and identified patients with postoperative atrial fibrillation who had been treated with a bisoprolol transdermal patch. We excluded patients with sinus rhythm using bisoprolol transdermal patch to prevent atrial fibrillation recurrence and those with sustained atrial fibrillation before surgery. Data on heart rhythm, heart rate, and blood pressure at the baseline and after 24 h of treatment were obtained from the electronic health records. Results: Of the 603 patients treated with the bisoprolol transdermal patch, 61 patients with postoperative atrial fibrillation after noncardiac surgery were included. The bisoprolol transdermal patch was discontinued due to bradycardia in two patients (3.3%). In both cases, the heart rate increased after the removal of the bisoprolol transdermal patch and no additional treatment was necessary. Among the 61 patients, sinus rhythm was restored within 24 h of bisoprolol treatment in 47 patients (77.0%). The heart rate significantly decreased from 124.8 ± 26.3 bpm at the baseline to 78.9 ± 16.6 bpm at 24 h after treatment ( p  < 0.001). There were no significant differences in the systolic and diastolic blood pressures between patients before and at 24 h after treatment. Conclusion: The results of this study indicate that the bisoprolol transdermal patch is well tolerated and effective in patients with atrial fibrillation after noncardiac surgery.